Characterization of the epidemiological profile of patients with chronic kidney disease, served in a dialytic treatment unit in Campo Mourão-PR (Research, Society and Development, 2022)
A retrospective research through medical records of the 195 patients from a dialysis treatment unit in the city Campo Mourão-PR, with the objective of tracing the epidemiological profile of patients who had care between the months of January to August 2020. The high number of individuals with chronic kidney disease (CKD) has increased annually among the main causes stand out the systemic arterial hypertension (SAH) and diabetes mellitus (DM). After the total stoppage of renal functions, dialysis treatment required, by either hemodialysis or peritoneal dialysis, to remove excess fluids and catabolites. It was possible to observe in 195 patients evaluated that the etiology of CKD the most prominent is SAH (46.67%), followed by DM (35.38%), with a predominance of male and age group between 61 to 70 years (26.15%). We can evidence that systemic arterial hypertension and diabetes mellitus, are the main basic diseases for CKD, requiring the elaboration of public policies to raise awareness and prevent the atrisk population about the need for medical monitoring of the risk factors described.